Improving relationship–based practice, practitioner confidence and family engagement skills through restorative approach training. (October 2018) - Williams, Annie; Reed, Hayley; Rees, Gwyther; Segrott, Jeremy
Abstract: Restorative Approach (RA) is an ethos and process that has been linked to a reduction of interpersonal conflict and improved relationships in various service settings but whose use is little explored in family services. This paper describes the findings of an evaluation of a training programme; The Restorative Approaches Family Engagement Project that was delivered to voluntary sector family practitioners across Wales with the intent of increasing the use of RA amongst practitioners and agencies, raising practitioner confidence when working with vulnerable families, and improving the extent to which and how practitioners engage with families. The study employed mixed methods. Quantitative measures investigated pre- and post- training practitioner perceptions of confidence, levels of family engagement, and organisational attitudes to RA. Post-training focus groups explored practitioner opinion of RAFEP and perceived changes to service delivery and receipt. Findings suggest RAFEP training promoted practitioner understanding of RA and increased perceptions of confidence when working with families in four specific aspects: developing positive relationships with service users, increasing communication, identifying service user needs/goals, and facilitating change. Qualitative data indicated that practitioners attributed the increased confidence to the service delivery framework engendered by the training and associated tools which facilitated its use and improved family engagement. Whilst host organisations were generally supportive of practitioners attending RAFEP training there was little evidence that knowledge and use of RA had been fully integrated into practitioner host agencies unless the organisation had previously used a restorative ethos. Highlights: The effects of restorative approach training on the service delivery of family support practitioners. The training had a positive effect on family engagement by increasing the confidence of practitioners with families and family members. Training impacted through familiarisation with restorative values, skills and tools. The study suggests Restorative Approaches training can help embed and promote strength and relationship-based practice in family service provision.